Palaeo-earthquake events during the late Early Palaeozoic in the central Tarim Basin (NW China): evidence from deep drilling cores - He, Bizhu; Qiao, Xiufu; Jiao, Cunli; Xu, Zhiqin; Cai, Zhihui; Guo, Xianpu; Zhang, Yinli (Bogucki Wydawnictwo Naukowe, 2014)
Various millimetre-, centimetre- and metre-scale soft-sediment deformation structures (SSDS) have been identified in the Upper Ordovician and Lower-Middle Silurian from deep drilling cores in the Tarim Basin (NW China). These struc -tures include liquefied-sand veins, liquefaction-induced breccias, boudinage-like structures, load and diapir- or flame --like structures, dish and mixed-layer structures, hydroplastic convolutions and seismic unconformities. The deformed layers are intercalated by undeformed layers of varying thicknesses that are petrologically and sedimentologically similar to the deformed layers. The SSDS developed in a shelf environment during the early Late Ordovician and formed initially under shear tensile stress conditions, as indicated by boudinage-like structures; during the latest Ordovician, SSDS formed under a com -pressional regime. The SSDS in the Lower-Middle Silurian consist mainly of mixed layers and sand veins; they formed in shoreline and tidal-flat settings with liquefaction features indicating an origin under a compressional stress regime. By Silurian times, the centre of tectonic activity had shifted to the south-eastern part of the basin. The SSDS occur at different depths in wells that are close to the syn-sedimentary Tazhong 1 Fault (TZ1F) and associated reversed-thrust secondary faults. Based on their characteristics, the inferred formation mechanism and the spatial asso -ciation with faults, the SSDS are interpreted as seismites. The Tazhong 1 fault was a seismogenic fault during the later Ordovician, whereas the reversed-direction secondary faults became active in the Early-Middle Silurian. Multiple palaeo-earthquake records reflect pulses and cyclicity, which supports secondary tectonic activity within the main tectonic movement. The range of SSDS structures reflects different developments of tectonic activity with time for the various tectonic units of the centralbasin. The effects of the strong palaeo-earthquake activity coincide with uplift, fault activity and syn-tectonic sedimentation in the study area during the Late Ordovician to Middle Silurian.
Keywords: Soft-sediment deformation structures; Seismites; Palaeo-seismicity; Late Ordovician; Silurian; Tazhong 1 Fault; Tarim Basin